A Concise Algorithm for Calculating the Number of Microstates in a Bose System - Shi, Chuan; Wen, Jun (Asia Pacific Economic and Management Review, 2025)
Thermodynamic and Statistical Physics is a difficult professional course at the undergraduate level. Students often encounter incomprehensible concepts and complex calculations when studying this course. The number of microstates of a Bose system and its calculation method are difficult to understand. However, the method presented in Wang Zhicheng’s book is not concise enough and easily causes doubts among students. In this paper, by introducing the model of separating small balls with boards, the problem of identical particles occupying quantum states at the energy level is transformed. This makes the calculation process of the number of microstates of the Bose system more intuitive and well avoids some doubts existing in the method in Wang Zhicheng’s book. In addition, our method can also clearly show the physical connotation of the number of microstates of the Bose system.